Giải các phương trình:
----- Nội dung dịch tự động từ ảnh -----
2.7 Giải các phương trình:
a) \(\frac{x}{x - 2} = \frac{x - 6}{x - 4}\)
b) \(3x - 5 = \frac{2x - 5}{x - 2} = 1;\)
c) \(x + 1 - 4 + \frac{x^2 - 3}{1 - x^2} = 0;\)
d) \(2x + 3 = \frac{3}{5x - 3 - 4x - 6} = \frac{2}{5};\)
e) \(\frac{2}{5} = \frac{x^2 + 2x + 1}{x^2 - 2x + 1(1 - x^2)};\)
f) \(x + \frac{1}{x - 2} = 2.\)
2.8 Giải các phương trình:
a) \(\frac{1}{x - 1} - \frac{7}{x - 2} = \frac{1}{(x - 1)(2 - x)};\)
b) \(\frac{3}{x + 2} - \frac{1}{x - 1} + \frac{9}{(x + 2)(x - 1)} = 0;\)
c) \(x + \frac{x - 1}{x - 2} = 3 + \frac{1}{x - 2};\)
d) \(2x - 1 + \frac{6x - 2}{x - 2} = 0;\)
e) \(\frac{3}{x + 2} - \frac{1}{x - 1} = \frac{1}{(x - 1)(x - 3)}.\)